Erratum: Improving the Training of Frontline Extension Workers in Tanzania: A Pilot Curriculum Reform Initiative with the Ministry of Agriculture Training Institute at Ilonga - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Rodriguez, M. T., Erbaugh, M., Mattee, A., Msuya, C., Masambuka, F., & Cochran, G. (2019). Improving the Training of Frontline Extension Workers in Tanzania: A Pilot Curriculum Reform Initiative with the Ministry of Agriculture Training Institute at Ilonga. Journal of International Agricultural and Extension Education, 26(3), 105-120” was incorrect as published. The correct DOI is: 10.5191//jiaee.2019.26307